Efficient One-Pot Synthesis of 2,4-Disubstituted Thiazoles and Dimeric Thiazoles Directly from Acyl Chlorides and β-Azido Disulfides - Liu, Yi; Li, Zhi; Xie, Yichuan; He, Peng; Qiao, Junfei; Fan, Xinyuan; Du, Yuguo (Synthesis, 2017)
A simple and effective one-pot cascade procedure to provide 2,4-disubstituted thiazoles and symmetrical dimeric thiazoles directly from commercially available acid chlorides and β-azido disulfides in moderate to high yields is described. This cascade transformation consists of disulfide cleavage, thiocarbonylation, phosphine-promoted intramolecular Staudinger/aza-Wittig reaction and dehydrogenation to form the corresponding thiazoles. The application of our methodology is demonstrated by the concise two-step synthesis of anticancer agent SMART and its O-linked dimer in 64% and 46% overall yields, respectively. This directed cascade reaction could be easily handled and scaled up under mild conditions, enabling the construction of focused thiazole derivatives for further pharmacological evaluation.
Keywords: one-pot reaction; 2,4-disubstituted thiazole; dimeric thiazole; acid chloride; SMART